MEMORIZING SONG LYRICS IN PRIMARY EDUCATION DURING THE MUSIC LESSON - Stramkale, Ligita (Journal of Education Culture and Society, 2020)
Aim. The aim of the study is to identify what techniques students use to memorise song lyrics, how much time is needed to do that, and whether and in what way their parents help them learn the song. The theoretical part of the study analyses previous researches on memorisation in the context of general psychology, age-related psychology, and music psychology. Method. The empirical study involved 47 (N=47) second-grade students of the comprehensive school (25 girls and 22 boys). Three study questions are raised in this paper: what techniques do students use to learn how to memorise song lyrics? How much time does a student need to learn singing a song by heart? Do parents help students memorise the song lyrics and in what way? To answer these questions, after having sung a song by memory each student was asked to write an essay about his/her thoughts on how he/she had learned this song at home. The content analysis was used in order to process the information contained in the essays and thus obtain a concise and detailed description of the song memorising techniques. Results. As a result of the obtained data analysis, it was determined that the most commonly used memorising techniques were: reading the song lyrics, singing the lyrics, and repeating them several times. The study also revealed that slightly more than half of the students did not get any parental assistance to learn a song by heart. Conclusion. The students who learn to sing a part of a song by heart during music lessons need less time to learn the whole song at home when compared with those students who do not learn parts of the songs in class.